THEORETICAL FUNDAMENTALS OF FORMATION FORECASTING SKILLS OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the theoretical principles of forming of future teachers' prognostic skills.